Educational Speaking Technology Tools in English Pronunciation - khoiriyah, khoiriyah; Sholahuddin, Muhammad Firza Thoriq; Ananta, Benny Dele Bintang (LETS: Journal of Linguistics and English Teaching Studies, 2025)
Pronunciation is essential for effective oral communication, yet it is often underemphasized in EFL classrooms due to teachers’ limited time, confidence, and resources. Digital tools such as YouGlish and Merriam-Webster provide authentic pronunciation models and phonetic sopport that can enhance students’ pronunciation learning. This study investigated the effectiveness of educational speaking technology in pronunciation instruction and examined the perceptions of English language learners in using the technology during their learning process. A mixed-methods design was employed involving 21 students enrolled in the Speaking for Informal Interaction course. Data were collected through pronunciation pre- and post-tests and questionnaires, including open-ended items, to capture students’ perceptions. Quantitative data were analyzed using SPSS, while qualitative data from open-ended responses were examined through thematic analysis. The findings indicated a significant improvement in students’ pronunciation performance after using the educational technology tools. Students also reported gains in overall speaking ability, especially in pronunciation, vocabulary use, and confidence. The tools’ authentic pronunciation examples and phonetic guides contributed greatly to these improvements. The results lead to the conclusion that incorporating educational speaking technology into language teaching can substantially enhance pronunciation skills. A balanced approach that combines technology with guided practice is recommended to maximize learning benefits and minimize potential confusion for learners.